(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article analyzes the important historical and legal documents that served to ensure the independence of the Republic of Uzbekistan, the formation and development stages of the legal system of the country, the prospects for the development of the legislation of our independent state. The changes in the social, economic, political, legal and cultural life of the country are reflected in the legal system. The development of normative documents regulating the spheres of social life has been studied in four stages.